1999
DOI: 10.1152/jn.1999.81.4.1469
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of the Midbrain Raphe Nuclear Regulation of Serotonin Release in the Hamster Suprachiasmatic Nucleus

Abstract: Serotonin (5-HT) plays important regulatory roles in mammalian circadian timekeeping; however, little is known concerning the regulation of serotonergic activity in the circadian clock located in the suprachiasmatic nuclei (SCN). By using in vivo microdialysis to measure 5-HT release we demonstrated that electrical or pharmacological stimulations of the dorsal or median raphe nuclei (DRN and MRN, respectively) can alter basal release of 5-HT in the hamster SCN. There were similar increases in SCN 5-HT release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 53 publications
(64 reference statements)
2
42
0
1
Order By: Relevance
“…Indeed, serotonin neurons from the midbrain raphe nuclei innervate the SCN, and local applications of 5-HT or 5-HT 1A and 7 receptor agonists to the SCN will also produce a phase advance in circadian activity (Dudley et al, 1999;Ehlen et al, 2001). Thus antidepressants in the selective serotonin reuptake inhibitor (SSRI) class may also exert some of their effects on depression through modulation of the circadian clock.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Indeed, serotonin neurons from the midbrain raphe nuclei innervate the SCN, and local applications of 5-HT or 5-HT 1A and 7 receptor agonists to the SCN will also produce a phase advance in circadian activity (Dudley et al, 1999;Ehlen et al, 2001). Thus antidepressants in the selective serotonin reuptake inhibitor (SSRI) class may also exert some of their effects on depression through modulation of the circadian clock.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Nonspecific excitation by passive current spread from the DRN to the MRN was evaluated previously using electrodes aimed ϳ0.8 mm dorsolateral to the MRN (Dudley et al, 1999). Stimulation from these electrodes did not affect SCN 5-HT release; therefore, it is unlikely that passive current flow from electrodes in the DRN would affect MRN neurons located farther away (ϳ2.0 mm ventral) from the stimulation site.…”
Section: Brain Implant Specificity Considerationsmentioning
confidence: 99%
“…Diffusion of drugs between the DRN and MRN was evaluated by comparing responses of the different nuclei with the same doses of drugs. The differential effects obtained [i.e., threefold greater response to 8-OH-DPAT or WAY 100635 injections into the MRN versus the DRN (Dudley et al, 1999)] indicate that the effects of the drugs were registered primarily at the site of injection. Also, the lack of effect of DRN injections that were off target by ϳ1 mm supports this contention.…”
Section: Brain Implant Specificity Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that serotonin neurons from the midbrain raphe nuclei innervate the SCN, and local applications of 5-hydroxytryptamine (5-HT) or 5-HT1A and 5-HT7 receptor agonists to the SCN will also produce a phase-advance in circadian activity (Dudley et al 1999;Ehlen et al 2001). Thus, it is possible that antidepressants in the selective serotonin reuptake inhibitor (SSRI) class may also exert some of their effects on depression through modulation of the circadian clock.…”
Section: Treatments For Mood Disorders Involve the Clockmentioning
confidence: 99%